Neurotoxicity and Cytokine Release Syndrome After Chimeric Antigen Receptor T Cell Therapy: Insights Into Mechanisms and Novel Therapies - Siegler, Elizabeth L.; Kenderian, Saad S. (Frontiers in Immunology, 2020)
Chimeric antigen receptor T (CART) cell immunotherapy has been remarkably successful in treating certain relapsed/refractory hematological cancers. However, CART cell therapy is also associated with toxicities which present an obstacle to its wider adoption as a mainstay for cancer treatment. The primary toxicities following CART cell administration are cytokine release syndrome (CRS) and immune effector cell-associated neurotoxicity syndrome (ICANS). New insights into the mechanisms of these toxicities have spurred novel treatment options. In this review, we summarize the available literature on the clinical manifestations, mechanisms, and treatments of CART-associated CRS and ICANS.